Brown rust (Puccinia triticina) and powdery mildew (Blumeria graminis) resistance of the winter durum wheat varieties at ARC “Donskoy” - T. G. Derova; N. V. Shishkin; O. S. Kononenko; N. E. Samofalova (Зерновое хозяйство России)
In order to increase food grain production of winter durum wheat, which is of high quality for producing cereals and pasta, it is necessary to increase the sown areas, which require varieties that meet the requirements of modern production to develop highly productive varieties with specified grain quality parameters and resistance to diseases. Both for bread wheat and durum wheat the harmful diseases are leaf rust and powdery mildew. The generally accepted methods of fighting them is the development of pathogen resistant varieties. Breeding for the resistance of this crop has been carried out at the FSBSI Agricultural Research Center “Donskoy” since the middle of the last century, as a result of which there were developed the varieties with the constantly increasing level of resistance. Through different years, there were developed and sown the varieties ‘Novinka 5’, ‘Donchanka’, ‘Donskoy yantar’, ‘Terra’, ‘Agat Donskoy’, ‘Lazurit’ which were not infected by brown rust and powdery mildew. The purpose of the study was to identify new reliable sources of resistance to these diseases in order to use them in breeding programs for immunity. The study was carried out on infectious backgrounds in 2015–2021, using the North Caucasian populations of leaf rust and powdery mildew pathogens. In the trials there were identified 63 winter durum wheat varieties of different ecological and geographical origin from inter-station variety testing, 26 powdery mildew resistant varieties, 20 leaf rust resistant varieties and 17 varieties resistant to both pathogens. Among the identified varieties with group resistance there are both the Russian varieties ‘Krucha’, ‘Kermen’, ‘Krupinka’, ‘Dobryana’ and others, and foreign varieties ‘Akveduk’, ‘Andromeda’, ‘Kassiopeya’, ‘Afina’, Pributkova and others.